Acolhimento residencial em Portugal - Rodrigues, Sónia (2019)
In Portugal there are 8000 children and young people in Residential Care (RC). The concept of RC quality emerges as the adequacy of the characteristics of the centres to the needs of children. Being a complex and multidimensional construct requires different perspectives and an evaluation by various sources, assuming the voice of children as the main reference in measuring the quality. The quality of the RC is closely related to psychological adjustment, well-being and satisfaction with life of children and adolescents. Until now it has not been performed in Portugal an assessment of the quality of the RC system. At this time there is an ongoing study that aims to assess the quality of Portuguese RC system through needs assessment and psychological adjustment of children in RC, the evaluation of the quality of services provided by centres and understanding of the relationship between these two variables. This symposium aims to present some emerging results of the pilot study of national character research, still in progress, which aims to assess the quality of the RC Portuguese system. In this sense, a brief contextualization of the RC will be in Portugal, followed by the presentation of the main methodology that is used for this assessment – A Comprehensive Evaluation System for Residential Care in Portugal (ARQUA-P). Subsequently, it will be presented the data related to the psychological adjustment of adolescents that are in RC, their self-esteem, well-being and happiness subjective, relating these variables with the quality of the RC.